3D printing concrete based on lithium slag and preparation method thereof

By rationally preparing 3D printed concrete based on lithium slag, the problems of high carbon emissions and insufficient early strength caused by high cement consumption are solved, and low-carbon and environmentally friendly 3D printing materials are achieved, which significantly improves the early strength and printability of concrete. .

CN119219393AActive Publication Date: 2024-12-31CHINA MCC17 GRP CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411337038.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-31
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

The amount of cement used in existing 3D printed concrete is too high, resulting in high carbon emissions and insufficient early strength, affecting constructability and making it difficult to meet the needs of 3D printing.

Method used

Using 3D printed concrete based on lithium slag, the preparation of LC3 cement and lithium slag is reasonably regulated, including silicate cement, magnesium phosphate cement, fly ash, calcined clay, limestone powder, lithium slag, gypsum and PVA fiber and other components. , and wet carbonization treatment is carried out to improve the early strength and printability of concrete.

Benefits of technology

It significantly reduces carbon emissions and energy consumption, improves the early strength and printability of concrete, realizes the recycling of solid waste and the environmentally friendly preparation of 3D printing materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219393A_ABST
    Figure CN119219393A_ABST
Patent Text Reader

Abstract

The invention discloses 3D printing concrete based on lithium slag and a preparation method thereof, and belongs to the field of civil engineering materials. The invention aims to reduce carbon emission and improve printability of traditional concrete in 3D printing application, and the concrete material comprises the following components: 45-50 parts by mass of ordinary Portland cement, 10-15 parts by mass of magnesium phosphate cement, 25-30 parts by mass of fly ash, 25-30 parts by mass of calcined clay, 10-18 parts by mass of lithium slag, 3-6 parts by mass of limestone powder, 3-5 parts by mass of gypsum, and 1-3 parts by mass of PVA fiber. 80-150 parts by mass of natural sand, 0.1-0.5 part by mass of a water reducing agent and 1-2 parts by mass of an early strength agent. The compressive strength of the prepared 3D printing low-carbon concrete material in 28 days is higher than 50 MPa, the carbon dioxide emission can be reduced by 43.6%, the energy consumption can be reduced by 29.4%, solid waste recycling is achieved, carbon emission can be remarkably reduced, and the environment is benefited while the cost is controlled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of civil engineering materials, and more specifically, to 3D printed concrete based on lithium slag and a preparation method thereof. Background Art

[0002] 3D printing is a new type of additive manufacturing process. It converts digital models into physical objects and adds materials layer by layer to build three-dimensional objects, thereby achieving highly customized and complex shape manufacturing. It is widely used in industrial manufacturing, healthcare, aerospace, automobile manufacturing, national defense science and technology and other fields. At present, 3D printing concrete technology has been widely used in the construction industry, greatly improving production efficiency and construction speed. Compared with traditional concrete construction, 3D printing technology has the advantages of fast construction speed, low cost, template-free construction, saving resources and labor costs, safe construction, high degree of construction freedom, and complex modeling design.

[0003] However, 3D printing technology has certain defects. The most commonly used cementitious material in 3D printing is cement. In existing 3D printed concrete, the amount of cement used is twice that of poured concrete. The production process of cement consumes huge amounts of energy and produces a large amount of greenhouse gases. Every ton of cement produced emits about 0.86 tons of CO2 gas into the atmosphere. Therefore, finding a suitable cement substitute is an important direction for reducing carbon emissions.

[0004] Limestone Calcined Clay Cement (LC3) uses calcined clay, limestone powder and gypsum to replace part of the cement clinker, which can effectively improve the economic and ecological benefits of cementitious materials. Compared with the currently widely used ordinary Portland cement, LC3 can reduce up to 30% of carbon dioxide emissions and 15% to 20% of energy consumption in the production of ordinary Portland cement due to its lower cement clinker content (no more than 50%). With the continuous maturity of this technology, LC3 has gradually become the most promising alternative to traditional ordinary Portland cement. However, due to the significant reduction in the amount of clinker in LC3 cement, its early strength is lower than that of ordinary Portland cement. In the 3D printing process, the bottom concrete will develop slowly and cannot effectively support the gravity of the upper concrete, resulting in obvious deformation, affecting the constructability, which greatly limits its good application in the field of 3D printing. Summary of the invention

[0005] 1. Technical problem to be solved by the invention

[0006] In view of the fact that conventional limestone powder calcined clay cement in the prior art is difficult to meet the needs of 3D printing, the present invention intends to provide a 3D printed limestone powder calcined clay low-carbon concrete based on lithium slag and a preparation method thereof, which can realize the utilization of solid waste and significantly reduce the carbon emissions of materials. By adding admixtures, the material properties can be regulated to make the material have good printability and meet the requirements of 3D printing.

[0007] 2. Technical solution

[0008] Lithium slag is waste residue produced in the process of preparing lithium products, and its appearance is milky white. The production of 1 ton of lithium carbonate produces about 10 tons of lithium slag, but the utilization rate of lithium slag is low. Due to the high content of SiO2 and Al2O3 in lithium slag, lithium slag has high activity. When used as a concrete mineral admixture, SO4 2- It can react with Ca(OH)2 produced by cement hydration to generate smaller crystalline hydrated calcium sulfoaluminate, which can be filled in the pores to improve the pore structure of concrete, reduce concrete shrinkage and permeability, and increase the elastic modulus of concrete. Moreover, lithium slag contains a large amount of Li element, which is the most active alkali metal element. It can accelerate the rate of hydration reaction in concrete and help improve the early strength of concrete. However, when lithium slag is used in 3D printed concrete, there are problems of high water content and high water demand, which affect the extrudability of 3D printed concrete during use. How to formulate low-carbon, environmentally friendly and printable 3D printed concrete materials through the reasonable regulation of LC3 cement and lithium slag is of great significance to the realization of sustainable development of construction, and has urgent technical development needs and broad market application prospects.

[0009] Based on this, the lithium slag-based 3D printing concrete provided by the present invention includes the following components in parts by weight:

[0010] Portland cement: 45-50 parts by weight, in practice, 45, 46, 48, 50 parts by weight can be used;

[0011] Magnesium phosphate cement: 10-15 parts by weight, in practice, 10, 12, 14, 15 parts by weight can be used;

[0012] Fly ash: 25-30 parts by mass, in practice, 25, 26, 28, 30 parts by mass can be used;

[0013] Calcined clay: 25-30 parts by weight, in practice, 25, 26, 28, 30 parts by weight can be used;

[0014] Limestone powder: 3-6 parts by weight, in practice, 3, 4, 5, 6 parts by weight can be used;

[0015] Lithium slag: 10-18 parts by weight, in practice, 10, 12, 15, 18 parts by weight can be used;

[0016] Gypsum: 3-5 parts by weight, in practice, 3, 4, 4.5, 5 parts by weight can be used;

[0017] PVA fiber: 1-3 parts by weight, in practice, 1, 2, 2.5, 3 parts by weight can be used;

[0018] Natural sand: 80-150 parts by weight, in practice, 80, 100, 130, 150 parts by weight can be used;

[0019] Water reducing agent: 0.1-0.5 parts by mass, in practice, 0.1, 0.2, 0.4, 0.5 parts by mass can be used;

[0020] Early strength agent: 1-2 parts by mass. In practice, 1, 1.2, 1.5, or 2 parts by mass can be used.

[0021] Furthermore, the silicate cement is ordinary silicate cement, the 28d compressive strength is 40-45MPa, and the water content of the standard consistency is 22-27%.

[0022] Furthermore, the initial setting time of magnesium phosphate cement is 8 to 10 minutes, and in practice, 8, 9, 10 minutes, etc. are used; the 1d compressive strength is 50 to 55 MPa, and the flexural strength is 7.5 to 8.1 MPa.

[0023] Furthermore, the specific surface area of ​​fly ash is 740-748m 2 / kg, particle size range is 0.55~80.68μm; or / and, specific surface area of ​​limestone powder is 197~226m 2 / kg, with a particle size range of 4.19 to 136.21μm. Lithium slag is waste slag produced in the process of preparing lithium products. Its main components are SiO2, Al2O3, and SO3, with a particle size of 0.47 to 69.36μm. Calcined clay is made from kaolin tailings collected in industrial tests and calcined at 700℃ to 800℃. Its main components are illite and quartz, of which SiO2 and Al2O3 account for 82% to 87%.

[0024] Furthermore, the diameter of PVA fiber is 0.01mm-0.0015mm and the density is 2.6-2.7g / cm 3 , length is 3~3.5mm, and tensile strength is 2080~2100MPa.

[0025] Furthermore, the average particle size of natural sand is 100-290 μm, the fineness modulus is 2.2-2.6, and the apparent density is 2600-2630 kg / m 3 .

[0026] Furthermore, the water reducer is a polycarboxylic acid solid water reducer with a water content of less than 3% and a water reduction rate of greater than 30%; or / and, the early strength agent is one or a mixture of a calcium formate water reducer and an anhydrous calcium sulfate water reducer, which is a white powder with a chemical purity of more than 90%; the thickener is carboxypropyl methylcellulose with a pH of 5.0 to 7.5, a viscosity of 40,000, a water content of less than 5%, and a fineness greater than 80 mesh.

[0027] The present invention also provides a method for preparing the above-mentioned lithium slag-based 3D printing concrete, comprising:

[0028] S1, wet carbonization treatment of lithium slag, then adding silicate cement, magnesium phosphate cement, fly ash, calcined clay, limestone powder, completely carbonized lithium slag, gypsum and natural sand into a mixer and uniformly mixing, and ball milling the mixture;

[0029] S2, prepare an early strength agent solution and a water reducing agent solution respectively, add both solutions to the dry material mixture after ball milling, and continue to stir evenly; specifically, add the early strength agent to the water and stir and mix quickly, add the water reducing agent to the water and stir and mix quickly, then add the two solutions respectively, and stir at a low speed until mixed;

[0030] S3. Add PVA fiber into the mixture and mix well.

[0031] Furthermore, the process of wet carbonization of lithium slag in S1 is:

[0032] S11, pre-carbonization treatment, the lithium slag is soaked in saturated lime water for 20-24 hours, such as 20 hours, 22 hours, 24 hours, etc. in practice, the volume of the lime water is 2 to 3 times the volume of the lithium slag, such as 2 times, 2.5 times, 3 times, etc. in practice;

[0033] S12, drying: placing the lithium slag carbonized with lime water in an oven for drying until the water content of the lithium slag is 4% to 6%, such as 4%, 5%, 6%, etc.;

[0034] S13, rapid carbonization: transfer the lithium slag powder to the carbonization chamber for further carbonization, the temperature is 75-80°C, the relative humidity is 60-70%; the CO2 concentration is 20%-40%, such as 20%, 30%, 40%, etc.; the duration is 2-3h, such as 2h, 2.5h, 3h, etc.;

[0035] S14, carbonization test: After carbonization is completed, 1% phenolphthalein indicator is sprayed on the lithium slag. If the color of the indicator does not change, it means complete carbonization, otherwise repeat steps S11-S13.

[0036] Furthermore, in step S1, the mixed material is ball-milled to a specific surface area of ​​not less than 550 m 2 / kg; in S2, the early strength agent solution and the water reducing agent solution are added to the dry material mixture three times each; in step S3, the PVA fiber is added three times and stirred at a low speed until it is mixed, and the fiber is well dispersed in the concrete paste without agglomeration.

[0037] To ensure that low-carbon concrete has good constructability, it needs to have a faster static yield stress growth rate. To ensure that 3D printing concrete materials have good extrudability, they need to have a lower dynamic yield stress within a certain range. The main component of lithium slag is SiO2, and the secondary component is Al2O3. The activity coefficient and basicity coefficient are low. Direct carbonization will result in shallow carbonization depth, and only surface carbonization will occur. The carbonization method of pre-immersion in lime water can provide additional Ca for lithium slag during the immersion process. 2+ ions, generate more carbonization products, increase the speed and depth of carbonization reaction, and in the process of carbonization, hydration products such as Ca(OH)2 are converted into CSH gel and high-density CaCO3 crystals, which fill the pores, reduce the porosity of the material and optimize the pore structure, increase the molar volume of lithium slag, and significantly reduce the water absorption rate of lithium slag. In addition, the material is added with ground fly ash, which is evenly distributed in a spherical shape, and there is a ball effect, which can reduce the friction between particles and increase the fluidity of the slurry, so as to improve the extrudability of concrete. In addition, carbonization increases the surface area of ​​lithium slag, and forms calcite crystals in the adhered cement paste area, and generates a large amount of calcium sulfonate. Needle-shaped AFt and honeycomb CSH gels continue to grow and wrap calcite crystals, so that the adsorption of water molecules on their surfaces increases. This leads to a reduction in the amount of free water in the fresh paste, reduces the charge on the surface of particles in the slurry, increases the Coulomb force between the colloid particles, increases the static yield stress, and is beneficial to the buildability of the material.

[0038] In addition, the main components of LC3 cement are limestone powder and calcareous clay. Limestone powder mainly provides Ca in the hydration reaction. 2 +, while calcareous clay needs a long time to hydrate to form a hydrated silicate phase, which is not conducive to the development of early strength, resulting in insufficient early hydration reaction and slow strength development. Since calcined clay has a lamellar structure and a large specific surface area, when it is added with water to form a cement mixture, due to its high solubility, it will release a large number of charged cations into the cement slurry, destroying the original water structure and forming a certain layer of water molecules around it, which attracts the negatively charged calcined clay layer, resulting in poor water flow ability, affecting the rearrangement and combination of cement particles, resulting in slow strength development. The early strength is lower than that of ordinary silicate cement. Adding a certain amount of magnesium phosphate cement and early strength agent can promote the development of early strength of the material. Its mechanism of action is that the early strength agent, as a strong electrolyte, can enhance the ion concentration of the cement liquid phase, play a role in expanding the compression of the double electron layer, and react with C3A and SO in the cement. 2-The reaction generates calcium sulfonate, which promotes the decomposition of C3A and accelerates the hydration reaction. It reacts with Ca(OH)2 to generate NaOH, which increases the pH value of the cement system and the Ca in the liquid phase. + Concentration promotes the formation of AFt and AFm, thus achieving the effect of rapid coagulation and improving early strength;

[0039] The present invention refines the particles by mechanical grinding, and the Si-O bonds and Al-O bonds in the lithium slag are destroyed, thereby changing the structure and performance of the concrete. The surface energy of the powder particles is changed, the crystal structure is distorted, and the crystal structure defects are increased, which is beneficial to improving the activity of the material. The amorphous silicon-aluminum components in the lithium slag have a certain volcanic ash activity, which can react with the calcium hydroxide in the cement hydration product to form a hydrated calcium silicate gel, which can improve the bonding property of the hydration product, thereby reducing the cracks in the cement hardened paste caused by the weak connection between the calcium hydroxide layers, and then improving its strength. The hydration reaction generally occurs in the middle and late stages, so the mechanical properties of the cement in the later stages can be improved, and the durability can be improved.

[0040] 3. Beneficial effects

[0041] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:

[0042] (1) The preparation method of 3D printed concrete based on lithium slag of the present invention uses LC3 limestone powder to calcine clay cement, and adds industrial solid waste lithium slag. It is calculated that it can reduce carbon dioxide emissions by 43.6% and energy consumption by 29.4%. It not only realizes the recycling of solid waste, but also can significantly reduce carbon emissions, which is beneficial to the environment while controlling costs.

[0043] (2) The preparation method of 3D printed concrete based on lithium slag of the present invention introduces additional Ca 2+ ions, which improve the effect of carbonization reaction and increase the carbonization depth by 78.2%. After wet carbonization treatment, the dynamic yield stress of concrete is reduced by 42.2%, the static yield stress is increased by 41.38%, and the early strength is increased by 74.7%, which significantly improves the printability and early strength of concrete materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 Schematic diagram of the printable sample of 3D printed low-carbon concrete in an embodiment of the present invention. DETAILED DESCRIPTION

[0045] In order to further understand the content of the present invention, the present invention is described in detail in conjunction with the accompanying drawings.

[0046] In the description of the present invention, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and "third" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.

[0047] The present invention will be further described below in conjunction with the embodiments.

[0048] Example 1

[0049] The lithium slag-based 3D printed concrete of this embodiment includes the following components: 45 parts by mass of ordinary Portland cement, 15 parts by mass of magnesium phosphate cement, 25 parts by mass of fly ash, 30 parts by mass of calcined clay, 15 parts by mass of lithium slag, 5 parts by mass of limestone powder, 5 parts by mass of gypsum, 1.3 parts by mass of PVA fiber, 150 parts by mass of natural sand, 0.3 parts by mass of water reducer, and 2 parts by mass of early strength agent.

[0050] The method for preparing the above-mentioned 3D printing concrete based on lithium slag comprises:

[0051] S1. Wet carbonization treatment of lithium slag: ordinary silicate cement, fly ash, calcined clay, limestone powder, completely carbonized lithium slag and gypsum are added into a mixer and stirred at low speed for 1 to 2 minutes until the mixture is uniform; the mixed materials are ball milled to make their specific surface area not less than 550m 2 / kg;

[0052] The specific process of wet carbonization treatment is as follows: S11, pre-carbonization treatment: soak the lithium slag in saturated lime water for 24 hours, and the volume of lime water is twice the volume of lithium slag; S12, drying: the lithium slag carbonized with lime water is placed in an oven to dry until the moisture content of the lithium slag is 4%; S13, rapid carbonization: transfer the lithium slag powder to a carbonization chamber for further carbonization, the temperature is 80°C, the relative humidity is 70%, and the CO 2 The concentration is 20% and the duration is 3h; after carbonization is completed, an inspection is carried out to ensure that it has been completely carbonized.

[0053] S2. Add the early strength agent to the water and stir rapidly for 1 minute until the mixture is evenly mixed. Similarly, add the water reducer to the water and stir rapidly for 1 minute until the mixture is evenly mixed. Then, slowly add the two solutions to the ground dry material mixture three times each and stir at a low speed for 2 to 3 minutes until the mixture is evenly mixed.

[0054] S3. Add PVA fibers in three times and stir at low speed for 3 minutes until the mixture is evenly mixed and the fibers are well dispersed in the concrete paste without agglomeration.

[0055] The carbon emission factor of the prepared concrete is 0.151kgCO2 / kg.

[0056] Example 2

[0057] The preparation method of 3D printed concrete based on lithium slag in this embodiment is basically the same as that in Example 1, except that the 3D printed concrete in this embodiment includes the following components: 50 parts by mass of ordinary Portland cement, 12 parts by mass of magnesium phosphate cement, 25 parts by mass of fly ash, 26 parts by mass of calcined clay, 12 parts by mass of lithium slag, 5 parts by mass of limestone powder, 5 parts by mass of gypsum, 1.3 parts by mass of PVA fiber, 150 parts by mass of natural sand, 0.26 parts by mass of water reducer, and 1.5 parts by mass of early strength agent. When the lithium slag is pre-carbonized, the volume of lime water is 3 times the volume of the lithium slag; the moisture content of the lithium slag after drying is 6%; the temperature during rapid carbonization is 75°C, the relative humidity is 60%, and CO 2 The concentration is 40%, the duration is 2h, and the carbon emission factor of the prepared concrete is 0.163kgCO2 / kg.

[0058] Example 3

[0059] The preparation method of 3D printed concrete based on lithium slag in this embodiment is basically the same as that in Example 1, except that the 3D printed concrete in this embodiment includes the following components: 50 parts by mass of ordinary Portland cement, 10 parts by mass of magnesium phosphate cement, 25 parts by mass of fly ash, 30 parts by mass of calcined clay, 18 parts by mass of lithium slag, 6 parts by mass of limestone powder, 5 parts by mass of gypsum, 2 parts by mass of PVA fiber, 140 parts by mass of natural sand, 0.4 parts by mass of water reducer, and 2 parts by mass of early strength agent. When the lithium slag is pre-carbonized, the volume of lime water is 2.5 times the volume of the lithium slag; the moisture content of the lithium slag after drying is 5%; the temperature during rapid carbonization is 76°C, the relative humidity is 66%, and the CO 2 The concentration is 30%, the duration is 2.5h, and the carbon emission factor of the prepared concrete is 0.168kgCO2 / kg.

[0060] Comparative Example 1

[0061] The preparation method of the concrete in this comparative example is basically the same as that in Example 3, except that the concrete in this comparative example includes the following components: 55 parts by mass of ordinary Portland cement, 10 parts by mass of magnesium phosphate cement, 25 parts by mass of fly ash, 20 parts by mass of calcined clay, 10 parts by mass of lithium slag, 5 parts by mass of limestone powder, 5 parts by mass of gypsum, 1.3 parts by mass of PVA fiber, 150 parts by mass of natural sand, 0.2 parts by mass of water reducing agent, and 1.2 parts by mass of early strength agent. In this comparative example, the lithium slag is subjected to rapid carbonization treatment without pre-carbonization treatment, and the carbon emission factor of the prepared concrete is 0.177 kgCO2 / kg.

[0062] Comparative Example 2

[0063] The preparation method of the concrete of this comparative example is basically the same as the above embodiment, except that the concrete in this comparative example includes the following components: 70 parts by mass of ordinary Portland cement, 10 parts by mass of magnesium phosphate cement, 25 parts by mass of fly ash, 8 parts by mass of lithium slag, 5 parts by mass of limestone powder, 5 parts by mass of gypsum, 1.3 parts by mass of PVA fiber, 150 parts by mass of natural sand, 0.09 parts by mass of water reducing agent, and 1.2 parts by mass of early strength agent. The carbon emission factor of the prepared concrete is 0.275 kgCO2 / kg.

[0064] Comparative Example 3

[0065] The preparation method of the concrete in this comparative example is basically the same as the above embodiment, except that the concrete in this comparative example includes the following components: 45 parts by mass of ordinary Portland cement, 15 parts by mass of magnesium phosphate cement, 25 parts by mass of fly ash, 10 parts by mass of lithium slag, 30 parts by mass of calcined clay, 5 parts by mass of limestone powder, 5 parts by mass of gypsum, 1.3 parts by mass of PVA fiber, 150 parts by mass of natural sand, 0.3 parts by mass of water reducing agent, and 2 parts by mass of early strength agent. In this comparative example, the lithium slag is not carbonized. The carbon emission factor of the prepared concrete is 0.160kgCO2 / kg.

[0066] According to the above cases, the obtained concrete was subjected to performance tests, including:

[0067] 1. Making a test piece, including: inputting the 3D printed low-carbon concrete of each embodiment and comparative example into a 3D printer barrel to print a concrete test piece. The extruder head diameter is 20 mm, the printing speed is 9 m / min, and then observing the printing effect, observing whether the concrete slurry can be continuously and evenly extruded, and evaluating the extrudability of the 3D printed low-carbon concrete material by measuring the error between the actual width of the printed strip and the designed width, and evaluating the constructability of the 3D printed low-carbon concrete material by measuring the error between the actual height of the printed strip and the designed height;

[0068] 2. Making the finished product, including: curing the concrete specimen at room temperature for 24 hours after coating, and then placing it in a standard curing room for 28 days to obtain the finished concrete product, wherein the condition of the standard curing room is 18-22° C. and the relative humidity is 90-95%.

[0069] According to the national standards "Standard for Test Methods for Performance of Ordinary Concrete Mixtures" (GB / T 50080-2016), "Test Method for Fluidity of Cement Mortar" (GB / T 2419-2005), and "Standard for Test Methods for Performance of Ordinary Concrete Mixtures" (GB / T50080-2002), the configured low-carbon concrete materials were subjected to fluidity and rheological tests, and the mechanical properties referred to the "Test Method for Strength of Cement Mortar (ISO)" (GB / T 17671-2021), and the printable performance test method referred to the "3D Printing Concrete Mixture Performance Test Method" (T / CBMF 184-2022). The results are shown in Table 1 below.

[0070] Table 1. Printing performance and mechanical properties of concrete

[0071]

[0072]

[0073] According to the calculation results of carbon emission factors of each case, it can be seen that the use of LC3 cement and lithium slag can reduce carbon dioxide emissions by 40.7%, which not only realizes the recycling of solid waste, but also significantly reduces carbon emissions, which is beneficial to the environment while controlling costs;

[0074] It can be seen from Table 1 that wet carbonization treatment of lithium slag can significantly improve the effect of carbonization reaction, the carbonization depth is increased by 78.2%, the dynamic yield stress of concrete after wet carbonization treatment is reduced by 58.7%, the static yield stress is increased by 54.1%, and the early strength is increased by 16.1%.

[0075] It can be seen from Table 1 that LC3 cement and lithium slag can adjust the static yield stress and dynamic yield stress of concrete materials. The addition of magnesium phosphate cement and early strength agent can alleviate the slow development of early strength of concrete caused by the addition of LC3 and lithium slag, which helps to enhance the printability of 3D printed concrete.

[0076] The above is a schematic description of the present invention and its implementation mode, which is not restrictive and is only one of the implementation modes of the present invention, and is not actually limited thereto. Therefore, if a person skilled in the art is inspired by it and, without departing from the purpose of the invention, designs a structure and an implementation mode similar to the technical solution without creativity, they shall all fall within the protection scope of the present invention.

Claims

1. 3D printed concrete based on lithium slag, characterized in that: The following components are included in parts by weight: Portland cement: 45-50 parts by mass, Magnesium phosphate cement: 10-15 parts by weight, Fly ash: 25-30 parts by mass, Calcined clay: 25-30 parts by weight, Limestone powder: 3-6 parts by weight, Lithium slag: 10-18 parts by mass, Gypsum: 3-5 parts by weight, PVA fiber: 1-3 parts by weight, Natural sand: 80-150 parts by weight, Water reducing agent: 0.1-0.5 parts by mass, Early strength agent: 1 to 2 parts by mass.

2. The 3D printed concrete based on lithium slag according to claim 1, characterized in that: The 28d compressive strength of silicate cement is 40-45MPa, and the water consumption at standard consistency is 22-27%.

3. The 3D printed concrete based on lithium slag according to claim 1, characterized in that: The initial setting time of magnesium phosphate cement is 8 to 10 minutes, the 1d compressive strength is 50 to 55 MPa, and the flexural strength is 7.5 to 8.1 MPa.

4. The lithium slag-based 3D printing concrete according to claim 1, characterized in that: The specific surface area of ​​fly ash is 740~748m 2 / kg, particle size range is 0.55~80.68μm; or / and, specific surface area of ​​limestone powder is 197~226m 2 / kg, and the particle size range is 4.19~136.21μm.

5. The lithium slag-based 3D printing concrete according to claim 1, characterized in that: The diameter of PVA fiber is 0.01mm~0.0015mm, the density is 2.6-2.7g / cm3, the length is 3~3.5mm, and the tensile strength is 2080~2100MPa.

6. The lithium slag-based 3D printing concrete according to claim 1, characterized in that: The average particle size of natural sand is 100-290μm, the fineness modulus is 2.2-2.6, and the apparent density is 2600-2630kg / m 3 .

7. The lithium slag-based 3D printing concrete according to claim 1, characterized in that: The water reducer is a polycarboxylic acid solid water reducer with a water content of less than 3% and a water reduction rate of greater than 30%; or / and, the early strength agent is one or a mixture of a calcium formate water reducer and an anhydrous calcium sulfate water reducer; the thickener is carboxypropyl methylcellulose with a pH of 5.0 to 7.5, a viscosity of 40,000, a water content of less than 5%, and a fineness greater than 80 meshes.

8. The method for preparing 3D printed concrete based on lithium slag according to any one of claims 1 to 7, characterized in that: include: S1, wet carbonization treatment of lithium slag, then adding silicate cement, magnesium phosphate cement, fly ash, calcined clay, limestone powder, completely carbonized lithium slag, gypsum and natural sand into a mixer and uniformly mixing, and ball milling the mixture; S2, prepare an early strength agent solution and a water reducing agent solution respectively, add both solutions to the dry material mixture after ball milling, and continue to stir evenly; S3. Add PVA fiber into the mixture and mix well.

9. The method for preparing 3D printed concrete based on lithium slag according to claim 8, characterized in that: The process of wet carbonization of lithium slag in S1 is: S11, pre-carbonization treatment, the lithium slag is soaked in saturated lime water for 20-24 hours, and the volume of the lime water is 2-3 times the volume of the lithium slag; S12, drying: placing the lithium slag carbonized with lime water in an oven for drying until the water content of the lithium slag is 4% to 6%; S13, rapid carbonization: transfer the lithium slag powder to the carbonization chamber for further carbonization at a temperature of 75-80°C, a relative humidity of 60-70%, and CO 2 The concentration is 20% to 40% and the duration is 2 to 3 hours; S14, carbonization test: After carbonization is completed, 1% phenolphthalein indicator is sprayed on the lithium slag. If the color of the indicator does not change, it means complete carbonization, otherwise repeat steps S11-S13.

10. The method for preparing 3D printed concrete based on lithium slag according to claim 8, characterized in that: In step S1, the mixed material is ball-milled to a specific surface area of ​​not less than 550 m 2 / kg; in S2, the early strength agent solution and the water reducing agent solution are added to the dry material mixture in multiple times; in step S3, the PVA fiber is added in multiple times.

Citation Information

Patent Citations

  • Cement clinker and preparation method and application thereof

    CN106698982A

  • Lithium slag and gravel mixed cement concrete and preparation method thereof

    CN109133775A

  • Colorant suitable for 3D printing white cement-based material as well as use method and application thereof

    CN110078411A

  • Performance-controllable cement composite slurry and preparation method thereof

    CN113185256A

  • Green low-carbon concrete and preparation method thereof

    CN114890744A